Neo-Developmentalism Beyond Neoliberalism? Capitalist Crisis and Argentina's Development Since the 1990s - Féliz, Mariano (2012)
Argentina’s recent trajectory has provoked several discussions in the last few years. Most of them have centred on the character of the new mode of development presumed to have appeared in the wake of the crisis of neoliberal rule. This article provides an analysis of the changes and continuities in capitalist development in Argentina after the crisis of 2001. We provide extensive evidence regarding changes in the mode of development which, we propose, has shifted towards a neo-developmentalist alternative. While we argue that this strategy perpetuates capitalist domination, more importantly we stress that it also implies significant changes from the previous pattern of development. Particularly, the new mode of capitalist development creates a new set of public policies that mediate class-conflict in renewed ways.